2000
DOI: 10.2460/ajvr.2000.61.582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endurance training on standard and signal-averaged electrocardiograms of sled dogs

Abstract: Electrocardiographic changes reflected physiologic cardiac hypertrophy in these canine athletes in response to repetitive endurance exercise. The QRS duration increases in response to endurance exercise training and, therefore, may be of use in predicting performance in endurance activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
1
23
0
3
Order By: Relevance
“…Commonly, exercise may cause a decrease in heart rate and increased ventricular relaxation which presents as longer QT intervals. A study investigating the effects of a seven month endurance training program in dogs revealed an increase in QT intervals [52]. An acute resistance exercise resulted in a similar effect on QT c intervals [53].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, exercise may cause a decrease in heart rate and increased ventricular relaxation which presents as longer QT intervals. A study investigating the effects of a seven month endurance training program in dogs revealed an increase in QT intervals [52]. An acute resistance exercise resulted in a similar effect on QT c intervals [53].…”
Section: Discussionmentioning
confidence: 99%
“…29 Both inhibition of the parasympathetic and activation of the sympathetic nervous system act to increase heart rate and strength of contraction during exercise. 37,38 Murmurs evident on auscultation are frequently heard in highly trained dogs compared with untrained dogs. Venous return to the heart enhances vagal tone and causes left-and right-ventricular enlargement.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Changes such as physiologic murmurs, bradyarrhythmias, and cardiac chamber enlargement are thought to be associated with cardiac adaptations to sustained endurance exercise and not pathologic conditions. 38 Hypertrophy of the canine heart as a result of endurance training is believed to be a reversible event. 37,38 Murmurs evident on auscultation are frequently heard in highly trained dogs compared with untrained dogs.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…not in mice and rats. Some of these studies observed slowed heart rate, prolonged QT interval and ECG signs of cardiac hypertrophy in such animals [43], [44]. Whether a ventricular electrical remodeling leading to decreased repolarization reserve develops in these animals is not known, however, it has been speculated that in top endurance athletes, downregulation of potassium channels might occur [45].…”
Section: Discussionmentioning
confidence: 99%